Deciphering the Role of MEF2D Splice Forms During Skeletal Muscle Differentiation - Rakopoulos, Patricia (Université d'Ottawa / University of Ottawa, 2011)
Members of the Mef2 transcription factor family are extensively studied within the muscle field for their ability to cooperate with the myogenic regulatory factors MyoD and myogenin during muscle differentiation. Although it is known that Mef2 pre-mRNAs undergo alternative splicing, the different splice forms have not been functionally annotated. In this thesis, my studies aimed to characterize three Mef2D splice forms: MEF2Dα'β, MEF2Dαβ, MEF2Dαø. Our results show that MEF2D splice forms can be differentially phosphorylated by p38 MAPK and PKA in vitro. Gene expression analysis using cell lines over-expressing each Mef2D splice form suggests that they can differentially activate desmin, myosin heavy chain and myogenin expression. Mass spectrometry analyses from our pull-down assays reveal known and novel MEF2D binding partners. Our work suggests that Mef2D splice forms have overlapping but distinct roles and provides new insight into the importance of Mef2D alternative splicing during skeletal myogenesis.
Keywords: Myogenesis; Alternative splicing; Mef2; Muscle differentiation